(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
A full-diallel cross comprising eight varieties belonging to four different maturity groups was developed and generate the evaluated entries and studied for fifteen characters to assess their’ performance. Eighty-one entries comprising the crosses, reciprocals, selfs, parents and nine checks were evaluated at Kadawa under irrigation in two different sowing dates serving as two environments, they were arranged in 9 x 9 lattice design with three replications in each environment. The results of the study indicated that, SAMMAZ 27 x SAMMAZ 35, SAMMAZ 27 x SAMMAZ 17, SAMMAZ 36 x SAMMAZ 29, SAMMAZ 19 x SAMMAZ 27 and SAMMAZ 29 x SAMMAZ 19 are better and more suitable for early planting in environment one while SAMMAZ 19 x SAMMAZ 17, and SAMMAZ 36 x SAMMAZ 35 are better for late planting in environment two. There is a need to select different parental varieties for hybrid production for specific situations. Specific hybrids should be produced for particular planting dates under irrigation, and also Inter variety hybrid development programme is recommended as an effective breeding approach to exploit the heterotic potential of the varieties. SAMMAZ 35, SAMMAZ 37, SAMMAZ 17, SAMMAZ 36 and SAMMAZ 27 are the best combiners for early days to maturity and high yield. They are recommended for extraction of inbred lines for hybrid and composite variety development.